Method of Hand Movement Testing on Grafic Tablet - Аврунін, О. Г.; Селіванова, К. Г. (LUH, 2013)
Developed a specialized program, which is implemented on a standard personal computer with standard digital graphic tablet high-resolution complete with the pen (stylus). Using specialized program, we can identify changes in fine motor skills and to quantify the level of motor skills.
Keywords: hand movement; motor skills of hand; diagnostic reliability; digital graphic tablet